Awareness towards workplace safety and satisfaction level of welfare program among the staff in RISDA Palong Oil Palm Plantation(ESPEK), Negeri Sembilan / Nurul Baiyah Shapawi - Shapawi, Nurul Baiyah (Faculty of Plantation and Agrotechnology, 2016)
Employee welfare and safety is the important thing to measure in an organization. Employee will play the important role in the organization. If there is no employee, it is difficult for organization to run smoothly. This study will measure the awareness of workplace safety and satisfaction level of the welfare program among the staff. The objective of this study is to identify the type of staff welfare that provided by . management, to evaluate the awareness of the workplace safety among the plantation staff, to measure the satisfaction level of plantation staff toward the welfare program This survey has been done using the questionnaire in staff RISDA PALONG. Every staff have their own aware and satisfaction. Majority of the respondent are satisfied about the facilities that provided and moderately aware about the awareness of the workplace . This study shows that the facilities have positive correlation with the satisfaction. This study will help the management to care more about the staff welfare and identify the suitable welfare to give to the employee.